Active Agents of Police and Army as Forgotten Victims in the Colombian Transitional Justice - Vega-Pérez, Leonel Antonio; Páez-Martínez, Gina Johana; Álvarez-Molano, Diana Lucía (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Transitional justice, understood as the measures taken by a government after the conflict, have been taken up by the national government in the Peace Accords signed with the Revolutionary Armed Forces of Colombia (FARC); however, in this transitional justice, gaps have been found in the concept of victims and integral reparation, since it only understands as victims civilians and members of the Police and Army, who have been directly or indirectly affected by the internal armed conflict, leaving aside the consequences that the active subjects of the war can suffer with respect to their emotional and psychological health. Therefore, this paper aims to analyze if the active agents, especially members of the Police and Army, are victims of the internal armed conflict that must be taken into account as such in the so-called Colombian transitional justice.